(untitled) (Research, Society and Development, 2022)
The religious and spiritual dimension is a constituent part of human subjectivity and its study is presented in a complex and multifaceted way. The present work sought to answer the problem about the possible relationships between religious behavior and religious beliefs with genetic factors and also sought to reflect on the importance of the interaction between genes x environment in the dimension of personal health and sustainability. For this, a bibliographic survey methodology was used and the investigation method of narrative review of the literature was used, from the descriptors selected by the researchers, five articles met the research objectives and were selected to carry out a critical analysis and discussion of the findings. The selected articles presented data that indicate that polymorphisms in certain genes can put people at a greater susceptibility to environmental influences than other people without these polymorphisms, and this, when associated with a positive religious context, evidences positive attitudes. By observing this interaction, we reflect on the importance of a critical analysis of the environments to which people are inserted, as well as the importance of cultivating virtues and incentives for a healthy life within religious environments, as well as the possibility of spirituality as a mediation for paths of sustainability and nature preservation. It is concluded that for there to be a real and significant approximation between science and religion, the path of respect and ethics is fundamental, with interdisciplinarity as an axis for expanding research on the phenomenon of religiosity.